Clinical profile of ocular surface tumours at a tertiary care centre - Kochar, Anju; Khan, Arif; Khan, Nabab Ali (International Journal Of Community Medicine And Public Health, 2020)
Background: Corneal and conjunctival squamous lesions are uncommon but important because of their potential for causing ocular and even systemic morbidity and mortality. The ocular surface tumors can be congenital or acquired and show a broad spectrum ranging from non-neoplastic benign tumours and others demonstrate premalignant or malignant tumours such as Squamous cell carcinoma, Malignant Melanoma or Kaposi Sarcoma. The types and frequency of conjunctival tumours differ with demographic features such as age and race, systemic immune status, and chronic exposures, along with specific location within the conjunctiva. Objectives of this study was to study ocular surface neoplasm in terms of demographics, histopathological and clinical presentation. Methods: This histopathological, prospective biopsy specimen series comprised of 107 patients of either sex and all age groups presenting with conjunctival lesion either benign or malignant. The study was carried out from December, 2017 to December, 2019 in the Department of Ophthalmology, S. P. Medical College and Associated Group of Hospitals, Bikaner in collaboration with Pathology Department. All enrolled cases of conjunctival lesion were screened by consecutive sampling after obtaining written consent. Results: 39.25% patients had nevus followed by ocular surface squamous neoplasia (OSSN) (20.56 %). Various ocular surface neoplasia with respect to mean age, age group, occupation was statistically highly significant (p<0.05) whereas gender was statistically non-significant. On histopathological examination most common benign ocular surface neoplasia was nevus and most common malignant tumor was ocular squamous surface neoplasia (OSSN). Conclusions: A large variety of conjunctival lesions may appear in the eye with variable presentation, most common benign ocular surface neoplasia was nevus and most common malignant tumor was ocular squamous surface neoplasia.